Effect of Health Belief Model-Based Educational Intervention AboutBreast Cancer on Nursing Students' Knowledge, Health Beliefs andBreast Self-Examination Practice (International Journal of Studies in Nursing, 2018)
Background: Breast cancer is a global health emergency and it is the principal reason of cancer related deaths in Developing Countries owing to the prevailing cultural beliefs and lack of awareness among women. This study aimed to evaluate the effect of health belief model-based education about breast cancer on nursing students' knowledge, health beliefs and breast self-examination practice. Subjects and Methods: A quasi-experimental design was utilized. Setting: The study was conducted at the Faculty of Nursing, Benha University, Benha city. A purposive sample of 104 nursing students were included in the study and divided into a study group (52) and control group (52). Three tools were used for data collection; first tool: self-administrated questionnaire to collect data about the subjects' socio-demographic characteristics, and knowledge regarding breast cancer. Second tool: the health belief model scale. Third tool: an observation checklist to assess the nursing students' practice of breast self-examination. Results: A statistically significant differences were observed between the study and control groups regarding knowledge about breast cancer after educational intervention based on health belief model (t test = 19.53, P=0.000). The mean scores of perceived susceptibility, severity, benefits, cues for action, self-efficacy and total heath belief model were significantly higher in the study group compared to control group (P = 0.000). Moreover a statistically significant difference was observed between both groups regarding breast self-examination practice after educational intervention (t test = 31.266, P= 0.000). Conclusion and recommendation: The health belief model based education is an effective and efficient manner in enhancing girls’ breast self-examination practice and improving their knowledge level and health beliefs about breast cancer. Thus the current study recommends implementing health belief model based educational intervention about breast cancer at different stages of life and settings to reach all targeted women to fight the disease.